A SURVEY OF THE ORIENTAL WHITE-BACKED VULTURE GYPS BENGALENSIS IN THE PUNJAB PROVINCE, PAKISTAN - Khan, Aleem A.; Virani, Munir Z.; Oaks, J. Lindsay; Benson, Patrick C.; Gilbert, Martin; Watson, Rick T.; Risebrough, Robert W. (Journal of Research (Science), 2001)
During bird survey in Pakistan, a distance of 1809 kilometers was covered in the Punjab province between August 16-29, 2000. A total of 1366 Oriental White-backed Vultures WBV (0.76 WBV/Km) was estimated from the study area. Out of a total of 175 WBV observed at close quarters for head drooping behaviour (from 7 different sites), the overall proportion of droopers to non-droopers was 16.6%, (which is similar to what observed in Nepal and West Bengal, India). The proportion of drooping birds to non-drooping birds was significantly higher at sites in Pakistan close to the Indian border near Rajasthan than those further away from the Rajasthan border. Similarly, more deaths were reported at sites closer to the Rajasthan border than those further inland towards the Indus River